2003
DOI: 10.1051/0004-6361:20030256
|View full text |Cite
|
Sign up to set email alerts
|

Optical and radio behaviour of the BL Lacertae object 0716+714

Abstract: Abstract. Eight optical and four radio observatories have been intensively monitoring the BL Lac object 0716+714 in the last years: 4854 data points have been collected in the UBVRI bands since 1994, while radio light curves extend back to 1978. Many of these data, which all together constitute the widest optical and radio database available on this object, are presented here for the first time. Four major optical outbursts were observed at the beginning of 1995, in late 1997, at the end of 2000, and in fall 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
186
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 195 publications
(217 citation statements)
references
References 47 publications
30
186
0
1
Order By: Relevance
“…S5 0716+714 is a prominent blazar in optical bands and has shown variability on diverse timescales from minutes through hours to days (e.g. Heidt & Wagner 1996;Nesci et al 1998;Giommi et al 1999;Raiteri et al 1999;Raiteri et al 2003;Gupta et al 2008;Gupta et al 2012;Agarwal et al 2016) in radio to X ray bands (e.g. Wagner et al 1996;Raiteri et al 2003 and references therein).…”
Section: S5 0716+714mentioning
confidence: 99%
“…S5 0716+714 is a prominent blazar in optical bands and has shown variability on diverse timescales from minutes through hours to days (e.g. Heidt & Wagner 1996;Nesci et al 1998;Giommi et al 1999;Raiteri et al 1999;Raiteri et al 2003;Gupta et al 2008;Gupta et al 2012;Agarwal et al 2016) in radio to X ray bands (e.g. Wagner et al 1996;Raiteri et al 2003 and references therein).…”
Section: S5 0716+714mentioning
confidence: 99%
“…9 were derived from Abdo et al (2010a). The August 2008 SEDs indicate a faint, synchrotrondominated state of the source that we fitted with the rotating helical jet model by , see also Raiteri et al 1999Raiteri et al 2003;Ostorero et al 2004). This model has been used by Raiteri et al (2009) to fit the broad-band SED of BL Lacertae in December 2007-January 2008.…”
Section: Modelling the Sedmentioning
confidence: 99%
“…The authors constructed spectral energy distributions (SEDs) of BL Lacertae corresponding to various epochs where the source was in different brightness states, using both their own data and data from the literature. They applied the inhomogeneous, rotating helical jet model by , see also Raiteri et al 1999Raiteri et al 2003;Ostorero et al 2004) to fit the SEDs, and suggested that the broad-band A&A 524, A43 (2010) spectral properties of BL Lacertae may result from the combination of two synchrotron emission components with their self inverse-Compton emission, plus a thermal component from the disc. Subsequently, Capetti et al (2010) analysed optical spectra acquired in the same period with the 3.56 m telescopio nazionale galileo (TNG).…”
Section: Introductionmentioning
confidence: 99%
“…Ghisellini et al 1997;Raiteri et al 2003). Correlation between radio (at 5 GHz) and optical (at 650 nm) variability suggest that scintillation, a process that is not effective at high radio and optical frequencies, does not play a large part in the observed variability (Quirrenbach et al 1991;Wagner 2001).…”
Section: The Bl Lac Object S5 0716+714mentioning
confidence: 99%
“…Therefore, we require that the model spectrum must agree with the data Table 1. Historical data, as compiled by Ostorero et al (2006) and shown as grey symbols, at radio-to-optical frequencies are from Kuehr et al (1981), Waltman et al (1981), Eckart et al (1982), Perley (1982), Perley et al (1982), Lawrence et al (1985), Saikia et al (1987), Kuehr & Schmidt (1990), Moshir et al (1990), Hales et al (1991), Krichbaum et al (1993), Gear et al (1994), Hales et al (1995), Douglas et al (1996), Rengelink et al (1997), Zhang et al (1997), Riley et al (1999), Cohen et al (2002), Raiteri et al (2003); UV data from Pian & Treves (1993), Ghisellini et al (1997); X-ray data from Biermann et al (1992), Comastri et al (1997), Kubo et al (1998), Giommi et al (1999), Tagliaferri et al (2003), Pian et al (2005); and γ-ray data from McNaron-Brown et al (1995), Hartman et al (1999), Collmar (2006). at these two frequencies.…”
Section: Injection Of Electrons In a Double Power Lawmentioning
confidence: 99%